Elite interviewing in professional organizations. Issue 1 (26th October 2017) - Empson, Laura
ABSTRACT: Interviewing elites presents distinctive methodological challenges, which are exacerbated when interviewing elite professionals. These individuals (i.e. senior professionals and professionals in elite professional organizations) are typically relatively powerful, highly educated, and self-assured, and work in organizations which guard their external image very carefully. Over the past 25 years, I have interviewed many hundreds of senior professionals in elite professional organizations. For this article, I have reflected on my experiences and have asked senior professionals to reflect on their own experience of research interviews. Bringing together insights of both interviewees and interviewers, this article provides an opportunity for researchers to reflect upon and improve their professional practice when conducting elite interviews.